Human perception of different aspects of field hockey stick performance - Carre, M. J.; McHutchon, M. A. (The impact of technology on Sport II, 2008)
This study sought to apply the semantic differential approach of human perception analysis to measure hockey players` emotional responses to different hockey sticks in different play situations. Three phases of testing were carried out: The first phase involved players being given a set of sticks with varying physical properties. Players were asked to carry out a set of repeated ball-strikes before rating the sticks using a semantic differential questionnaire. The second phase of testing involved repeating the ball-strike study, but with the players` vision of the ball`s post-hit behaviour being impaired. This was carried out to assess the need for visual cues in assessing stick performance (e.g. power and accuracy). The final phase of testing involved player perception of dribbling performance and used a different set of disguised sticks, including some with mass-distributions that had been altered. The key findings were that players associate a heavy stick with a mass-distribution concentrated towards the head-end as being well suited to hitting. However, for dribbling, players prefer a stick with a centre of mass higher up the handle. Interestingly, visual cues of post-hit ball behaviour made little difference to a player`s ability to judge power and accuracy. Results from these studies have been incorporated into an all-encompassing design methodology for sports equipment.